2017
DOI: 10.1016/j.mam.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting nuclear thymidylate biosynthesis

Abstract: Thymidylate (dTMP) biosynthesis plays an essential and exclusive function in DNA synthesis and proper cell division, and therefore has been an attractive therapeutic target. Folate analogues, known as antifolates, and nucleotide analogs that inhibit the enzymatic action of the de novo thymidylate biosynthesis pathway and are commonly used in cancer treatment. In this review, we examine the mechanisms by which the antifolate 5-fluorouracil, as well as other dTMP synthesis inhibitors, function in cancer treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 121 publications
0
57
0
Order By: Relevance
“…Besides its role as a methyl group donor for the remethylation of homocysteine, CH 2 THF is also a source of methyl groups for the synthesis of thymidylate or deoxythimidine monophosphate (dTMP) from deoxyuridine monophosphate (dUMP). The net effect of reduced CH 2 THF may be impaired de novo dTMP synthesis and a greater rate of uracil misincorporation into DNA, resulting in single-and double-stranded breaks through the actions of DNA repair enzymes [60]. Our findings assume importance given previous studies implicating genome instability and impaired DNA repair in AD pathogenesis [61].…”
Section: Genementioning
confidence: 60%
“…Besides its role as a methyl group donor for the remethylation of homocysteine, CH 2 THF is also a source of methyl groups for the synthesis of thymidylate or deoxythimidine monophosphate (dTMP) from deoxyuridine monophosphate (dUMP). The net effect of reduced CH 2 THF may be impaired de novo dTMP synthesis and a greater rate of uracil misincorporation into DNA, resulting in single-and double-stranded breaks through the actions of DNA repair enzymes [60]. Our findings assume importance given previous studies implicating genome instability and impaired DNA repair in AD pathogenesis [61].…”
Section: Genementioning
confidence: 60%
“…Rather, it reveals a specific characteristic of cisplatin-resistant cells that be taken advantage of to kill them. More importantly from the therapeutic point of view, we observed that CDDP-resistant cells acquired an exquisite susceptibility to several chemotherapeutic agents that inhibit nucleotide metabolism such as 5-fluorouracil (5-FU, an inhibitor of thymidylate synthase; Chon et al, 2017) or clofarabine (CLO, an inhibitor of ribonucleotide reductase; Aye et al, 2015). Interestingly, a recent siRNA-based genetic screen also revealed that knockdown of ribonucleoside-diphosphate reductase subunit M2 B can sensitize cancer cells to CDDP as well (Leung et al, 2016), pleading in favor of the specificity of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…3 5-fluorouracil (5-FU) is currently a first-line agent for the clinical treatment of GC, which affects the de novo synthesis of DNA by multiple mechanisms, such as incorporation into RNA or DNA, and suppression of thymidine synthase, resulting in cell death. 4 Despite their overall efficacy, GC cells often develop resistance to 5-FU. Thus, novel strategies to overcome the resistance of GC cells to 5-FU are urgently needed.…”
Section: Introductionmentioning
confidence: 99%